Impact of Climate Change on Cultivar Choice: Adaptation Strategies of Farmers and Advisors in German Cereal Production - Macholdt, Janna; Honermeier, Bernd; Justus Liebig University Giessen (My University, 2016)
The objective of this study is to understand which requirements for cereal cultivars with regard to climate change adaptation are in demand by farmers and advisors, and to clarify whether there are any differences in their assessments. A comparative survey was used to collect data from 410 farmers and 114 advisors in Germany. The majority of both farmers and advisors reported perceivable effects of climatic change on plant production. The increase in droughts and hot spells, the increased incidence of torrential rain, and mild winters were mentioned as the main effects of climate change. For climate change adaptation, the farmers and advisors mostly relied on a locally-adapted cultivar selection. It is estimated that eco-stability, grain yield, resistance to lodging and drought tolerance are important cultivar properties. In the study, farmers and advisors equally pointed out the need for additional cultivar evaluation according to eco-stability. Finally, only minor differences regarding farmers and advisors assessments were found within the study. The outcome of this research points to the need of implementing farmers demands in cultivar recommendations. For example, an impartial assessment of cultivars eco-stability could help support the choice of cultivars and reduce the growing risks in cereal production with regard to climate change.
Keywords: survey; plant production; cultivar requirements; cultivar type; hybrid cultivars; ddc:630